2006
DOI: 10.1086/501518
|View full text |Cite
|
Sign up to set email alerts
|

Critical Metallicity and Fine‐Structure Emission of Primordial Gas Enriched by the First Stars

Abstract: The influence of the first stars on the formation of second-generation objects at high redshift may be determined, in part, by their metal enrichment of surrounding gas. At a critical metallicity, Z crit , primordial gas cools more efficiently by fine-structure lines of [C ii] (157.74 m), [O i] (63.18 m, 145.5 m), [Si ii] (34.8 m), and [Fe ii] (25.99 m, 35.35 m) than by H i or H 2 emission.This cooling may alter the process of fragmentation into smaller units. We study the time-dependent cooling of primordial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
198
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(208 citation statements)
references
References 49 publications
9
198
1
Order By: Relevance
“…Enriched halos have a more efficient cooling, which in turn favors fragmentation and star formation over the efficient collection of gas conducive to MBH formation. It has been suggested that efficient gas collapse probably occurs only in massive halos with virial temperatures T vir ∼ > 10 4 K under metal-free conditions where the formation of H 2 is inhibited (Bromm and Loeb, 2003), or for gas enriched below the critical metallicity threshold for fragmentation (Santoro and Shull, 2006). For these systems the tenuous gas cools down by atomic hydrogen only until it reaches Tgas ∼ 4000 K. At this point the cooling function of the atomic hydrogen drops by a few orders of magnitude, and contraction proceeds nearly adiabatically.…”
Section: Gas-dynamical Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Enriched halos have a more efficient cooling, which in turn favors fragmentation and star formation over the efficient collection of gas conducive to MBH formation. It has been suggested that efficient gas collapse probably occurs only in massive halos with virial temperatures T vir ∼ > 10 4 K under metal-free conditions where the formation of H 2 is inhibited (Bromm and Loeb, 2003), or for gas enriched below the critical metallicity threshold for fragmentation (Santoro and Shull, 2006). For these systems the tenuous gas cools down by atomic hydrogen only until it reaches Tgas ∼ 4000 K. At this point the cooling function of the atomic hydrogen drops by a few orders of magnitude, and contraction proceeds nearly adiabatically.…”
Section: Gas-dynamical Processesmentioning
confidence: 99%
“…The second condition implies that at low density H 2 is dissociated and does not contribute to cooling. The third condition ensures that gas can fragment and form low-mass stars only if the gas density is above a certain threshold, n crit,Z (which depends on the metallicity, see Santoro and Shull, 2006): this causes only the highest density regions of a proto-galactic disc (see section 2.3) to be prone to star formation.…”
Section: Stellar-dynamical Processesmentioning
confidence: 99%
“…Devecchi and Volonteri [83] showed that runaway collapse is a viable route for seed BH formation in mildly metal polluted (Z < 10 −3 Z ), efficient hydrogen cooling (T v > 10 4 K) halos at high redshift. Their scenario is similar to the direct collapse mechanism discussed above, with the difference that the mass accumulated in the central parsec overcomes the density threshold (function of the metallicity, see [84]) at which fragmentation and star formation occur efficiently. The most massive stars in the resulting compact cluster undergo runaway collisions forming a VMS of several thousand solar masses, leaving behind a seed BH remnant of ∼1000-2000 M .…”
Section: Runaway Stellar Dynamicsmentioning
confidence: 68%
“…Many gas and dust components are taken into account, among which we recall the molecular hydrogen and the metal coolants (Santoro & Shull 2006;Maio et al 2007) or HD (McGreer & Bryan 2008). To track the evolution of these components, the ISM model and robo take various physical processes into account that may affect the behavior of the whole system.…”
Section: Introductionmentioning
confidence: 99%